ナンキョク ショウワ キチ ノ ガンバン ボーリング - 神沼, 克伊; カミヌマ, カツタダ; Kaminuma, Katsutada (1983)
P(論文) 日本南極地域観測隊は, 第20-22次の「昭和基地を中心とする地域の地殻構造の総合解析」研究の一環として, 地温測定と地盤傾斜観測のために岩盤ボーリングを行った。第21次隊よりエアボーリングが開始され, 深さ20mの孔を得て地温測定が行われた。作業能率その他を考慮して第22次隊では水ボーリングを採用し, 深さ30mを目標とするボーリングを行った。しかし, 凍結のため孔内にロッドが抑留され地温測定用としては7m以深は使用できなくなった。さらに30mボーリングを試み, 2960cm孔の掘削に成功した。しかし, 孔内に残った掘削流体が凍結し, これを掘削中, またもロッドが抑留され, 結局, この孔は使用できなかった。凍結は, 予想以上の大量の逸水のため不凍液濃度を十分に保つことができず発生した。逸水または出水を防ぐことが, 今後昭和基地で岩盤ボーリングを再開する際もっとも重要な点である。 The first core drilling at Syowa Station in Antarctica was carried out by the 21st Japanese Antarctic Research Expedition (JARE-21) by a rotary core drilling method using air as the drilling fluid. After 26 days of drilling work, a 20m-deep borehole was obtained in March 1980. In order to deepen this borehole, the core drilling was succeeded by JARE-22 using water as the drilling fluid. However, drilling rods were stuck in the hole during the removal of the frozen drilling fluid. The part of the hole which is deeper than 5m could not be used for underground temperature measurements. Though a new 30m-deep hole was drilled in March 1981,drilling rods were stuck in the hole again. Only the upper part of the hole which is shallower than 7m could be used for the temperature measurements. Another 30m-deep hole was drilled in January 1982. It was done well to make the 30m-deep hole. However, the hole could not be used for the temperature measurements, because drilling rods were stuck in the hole again during the removal of the drilling fluid. Though the leakage and/or flood of water in the drilling hole on East Ongul Island was beyond prediction, a few cracks at the depth from the surface to 10m were found to act as waterways. To keep water from leakage and/or flood is the most important in the core drilling at Syowa Station. departmental bulletin paper